Social representations of the elderly about HIV/AIDS - Brígida Maria Gonçalves de Melo Brandão; Rebeca Coelho de Moura Angelim; Sergio Corrêa Marques; Denize Cristina de Oliveira; Regina Célia de Oliveira; Fátima Maria da Silva Abrão
ABSTRACT Objective: to understand the representational content about HIV/AIDS among seropositive elderly people. Method: a qualitative study carried out from April to May 2017, in the city of Recife/PE, with 48 seropositive elderly people, through a semi-structured interview. The Social Representations Theory was used as theoretical framework and the method of lexical analysis through IRAMUTEQ software. Results: it was observed that the social representation of HIV is structured around the proximity of death and that it is a disease of restricted groups, leading to feelings of sadness. On the other hand, it is evident a transformation of the representation linked to the reified knowledge, leading to the process of naturalization of the disease. Final considerations: it is concluded that the elderly living with HIV, when they undergo a process of reframing about the disease, become more flexible to deal with their condition of seropositivity.